Pure Land, Real World Modern Buddhism, Japanese Leftists, and the Utopian Imagination - Curley, Melissa Anne-Marie (Pure Land Buddhist Studies, 2018)
Such readings of the Pure Land tradition are idiosyncratic—perhaps even heretical—but they hum with the same vibrancy that characterized medieval Pure Land belief. Innovative and refreshingly accessible, Pure Land, Real World shows that the Pure Land tradition informed twentieth-century Japanese thought in profound and surprising ways and suggests that it might do the same for twenty-first-century thinkers. The critical power of Pure Land utopianism has yet to be exhausted